Phage therapy as a promising solution for food safety: isolation and biological characterization of bacteriophage P2 for controlling Salmonella enterica infections - Tran Khang Nam; Lanh, Pham Thi; Hong Phuoc, Man; Quyen, Dong Van (Academia Journal of Biology, 2025)
Food poisoning and foodborne illnesses not only directly impact human health and quality of life but also result in significant economic losses and healthcare costs. Among the factors causing food poisoning, bacteria are the most common, including Salmonella enterica, which belongs to the Enterobacteriaceae family. Salmonellosis, which is introduced by S. enterica infection, can lead to symptoms such as fever, diarrhea, vomiting, and, in severe cases, even death. Remarkably, S. enterica has developed a high level of antibiotic resistance. Hence, the imperative pursuit of a reliable approach capable of averting S. enterica infections has emerged as an important goal essential for ensuring public health safety. This study aims to identify bacteriophages capable of effectively controlling S. enterica. Ten phage strains were isolated, among which phage P2, classified under the Siphoviridae family, exhibited strong lytic activity and a broad host range. Phage P2 had an optimal multiplicity of infection (MOI) of 0.01, reaching a titer of about 8.4 × 109 PFU/mL. It displayed a latent period of 15 minutes and a burst size of 63 PFU/cell. Notably, phage P2 demonstrated tolerance to a wide range of conditions, including temperatures from 4 oC to 50 oC, pH levels from 2 to 12, and salt concentrations of 0.1 M–7 M. The in vitro lytic activity assay showed that phage P2 significantly reduced bacterial counts by 3.08 log CFU/mL compared to the control group after one hour of incubation at 37 oC. These findings highlight the potential of phage P2 as a promising biocontrol agent for food preservation.